2000
DOI: 10.1152/physrev.2000.80.4.1411
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Consequences of Potassium Shifts in Skeletal Muscle and Heart During Exercise

Abstract: Since it became clear that K(+) shifts with exercise are extensive and can cause more than a doubling of the extracellular [K(+)] ([K(+)](s)) as reviewed here, it has been suggested that these shifts may cause fatigue through the effect on muscle excitability and action potentials (AP). The cause of the K(+) shifts is a transient or long-lasting mismatch between outward repolarizing K(+) currents and K(+) influx carried by the Na(+)-K(+) pump. Several factors modify the effect of raised [K(+)](s) during exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
438
6
13

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(474 citation statements)
references
References 648 publications
17
438
6
13
Order By: Relevance
“…Potassium clearance during exercise also occurs via uptake by other non-contracting or relatively inactive muscles, and also splanchnic K + uptake (Lindinger 1995;Sejersted and Sjøgaard 2000;Clausen 2003 (Hostrup et al 2014a;Collomp et al 2000;Grove et al 1995;Newnham et al 1993;Van Baak et al 2000), or in samples drawn only after completion of, rather than during exercise (Hostrup et al 2014a;Kalsen et al 2014;Hostrup et al 2014b;Larsson et al 1997;Grove et al 1995); and/or utilised oral salbutamol (Collomp et al 2000;Van Baak et al 2000;Hostrup et al 2014a;Goubault et al 2001 after prolonged cycling to exhaustion (Van Baak et al 2000), or at 5-10 min recovery after repeated 30 s sprints or repeated bouts of high intensity cycling, although greater reductions were evident at 1 or 2 min after some individual bouts (Hostrup et al 2014a). Similarly, after salbutamol inhalation (800 µg), there was no further change in antecubital venous [K + ] at 2-10 min after exhaustive cycling at 85% VO 2peak (Goubault et al 2001).…”
Section: Blood Sampling and Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…Potassium clearance during exercise also occurs via uptake by other non-contracting or relatively inactive muscles, and also splanchnic K + uptake (Lindinger 1995;Sejersted and Sjøgaard 2000;Clausen 2003 (Hostrup et al 2014a;Collomp et al 2000;Grove et al 1995;Newnham et al 1993;Van Baak et al 2000), or in samples drawn only after completion of, rather than during exercise (Hostrup et al 2014a;Kalsen et al 2014;Hostrup et al 2014b;Larsson et al 1997;Grove et al 1995); and/or utilised oral salbutamol (Collomp et al 2000;Van Baak et al 2000;Hostrup et al 2014a;Goubault et al 2001 after prolonged cycling to exhaustion (Van Baak et al 2000), or at 5-10 min recovery after repeated 30 s sprints or repeated bouts of high intensity cycling, although greater reductions were evident at 1 or 2 min after some individual bouts (Hostrup et al 2014a). Similarly, after salbutamol inhalation (800 µg), there was no further change in antecubital venous [K + ] at 2-10 min after exhaustive cycling at 85% VO 2peak (Goubault et al 2001).…”
Section: Blood Sampling and Analysesmentioning
confidence: 99%
“…Salbutamol typically does not enhance performance during endurance exercise (Koch et al 2015;Pluim et al 2011), when K + disturbances are modest (Sejersted and Sjøgaard 2000), with some exceptions, where venous [K + ] was also reduced by ~0.2-0.4 mM (Van Baak et al 2000;Collomp et al 2000). Performance during a 30 s cycle sprint was enhanced by oral salbutamol (4-8 mg) (Le Panse et al 2007;Collomp et al 2005;Hostrup et al 2014a), with the post-exercise antecubital (Hostrup et al 2014a (Kalsen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pursuant to this consideration, and to more closely approach physiological conditions, Allen et al 16) investigated intracellular phosphate concentration ([P(i)]), measured by (31)P nuclear magnetic resonance (NMR) and myoplasmic and sarcoplasmic reticulum (SR) calcium concentrations during tetanic contractions, in in vivo mouse skeletal muscle. They showed that the initial phase of muscle fatigue is accompanied by a rise in [P(i)] and a decrease in tetanic myoplasmic calcium -a very different scenario from that observed in vitro 24,76,83,84) . Thus, a compelling case may be made for studying the mechanisms of muscle fatigue in vivo using contemporary models as and when they become available.…”
Section: Intracellular Ca 2+ and Muscle Fatiguementioning
confidence: 88%